2016
DOI: 10.1210/jc.2016-1504
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phenotype of Familial Hyperaldosteronism Type III: Concurrence of Aldosteronism and Cushing’s Syndrome

Abstract: We presented the first FH-III patient who had both severe PA and Cushing's syndrome. Hypersecretion of cortisol might be ascribed to overly large size of the hyperplastic adrenal because CYP11B1 expression was relatively low in his adrenal. Like aldosterone, synthesis and secretion of cortisol in the mutant adrenal may be mediated by voltage-gated Ca channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Yamada et al reported 2 female patients with APA co-secreting cortisol, without clinical signs of Cushing’s syndrome, which harbored mutations in KCNJ5 [4]. Tong et al described a patient with familial PA associated with overt Cushing’s syndrome, harboring a KNCJ5 germline mutations, who had a massive bilateral hyperplasia [48]. We could not confirm the presence of KCNJ5 mutations, as well as of mutations in other genes (i.e., ATP1A1 , ATP2B3 , CACNA1D ) involved in calcium signaling, in our series of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al reported 2 female patients with APA co-secreting cortisol, without clinical signs of Cushing’s syndrome, which harbored mutations in KCNJ5 [4]. Tong et al described a patient with familial PA associated with overt Cushing’s syndrome, harboring a KNCJ5 germline mutations, who had a massive bilateral hyperplasia [48]. We could not confirm the presence of KCNJ5 mutations, as well as of mutations in other genes (i.e., ATP1A1 , ATP2B3 , CACNA1D ) involved in calcium signaling, in our series of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the patient carrying the p.Tyr152Cys mutation displayed a less severe phenotype (31). Interestingly, a case of FH-III (due to the KCNJ5 p.Glu145Gln mutation) presenting with severe PA and tytpical Cushing's syndrome has recently been reported in a Chinese boy (32). In vitro electrophysiological studies showed that the p.Gly151Glu substitution was associated with a particularly severe impairment of the channel functioning, with massive Na + entry, osmotic shock and cell death.…”
mentioning
confidence: 99%
“…Different studies have identified germline KCNJ5 mutations in FH-III families with a phenotypic variability, ranging from spironolactone-responsive hyperaldosteronism to massive adrenal hyperplasia with drug-resistant hypertension (Choi et al 2011, Charmandari et al 2012, Mussa et al 2012, Scholl et al 2012, Monticone et al 2013, Adachi et al 2014, Tong et al 2016. This variability was attributed to the type of KCNJ5 mutation, with a severe phenotype associated with GIRK4 p.Gly151Arg, p.Thr158Ala, p.Ile157Ser and p.Tyr152Cys mutations, and a milder phenotype associated with KCNJ5 p.Gly151Glu mutations.…”
Section: Familial Hyperaldosteronism Type III and Germline Kcnj5 Mutamentioning
confidence: 99%
“…Combined aldosterone and cortisol oversecretion associated with massive bilateral adrenal hyperplasia was described in a patient carrying a germline KCNJ5 mutation (p.Glu145Gln) (Tong et al 2016). In primary cell culture of the resected hyperplastic adrenal, calcium channel blockers inhibited the secretion of both aldosterone and cortisol and the mRNA expression of steroidogenic enzymes.…”
Section: Familial Hyperaldosteronism Type III and Germline Kcnj5 Mutamentioning
confidence: 99%
See 1 more Smart Citation